2011
DOI: 10.1007/s10955-011-0164-4
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of Random Equilateral Polygons

Abstract: Freely jointed random equilateral polygons serve as a common model for polymer rings, reflecting their statistical properties under theta conditions. To generate equilateral polygons, researchers employ many procedures that have been proved, or at least are believed, to be random with respect to the natural measure on the space of polygonal knots. As a result, the random selection of equilateral polygons, as well as the statistical robustness of this selection, is of particular interest. In this research, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 65 publications
1
43
0
Order By: Relevance
“…There are a number of methods available for the random generation of equilateral knots [1]. Because we seek to have the arc close to give a ring polygon, we can't merely generate an arbitrary random walk.…”
Section: Previous Thickness Free Generation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of methods available for the random generation of equilateral knots [1]. Because we seek to have the arc close to give a ring polygon, we can't merely generate an arbitrary random walk.…”
Section: Previous Thickness Free Generation Methodsmentioning
confidence: 99%
“…Most methods come in two stages, an initialization stage, and a randomization stage. Two similar methods for initializing a closed polygon are the generalized hedgehog method, and the triangle method [1]. These involve randomly generating sets of two or three vectors which add to zero, and then randomly ordering these vectors.…”
Section: Previous Thickness Free Generation Methodsmentioning
confidence: 99%
“…In order to simulate an Olympic gel, we first create an unknotted random 125 edge equilateral polygon using the crankshaft algorithm [1]. The resulting polygon is randomly placed in the interior of a generating cell and extended to a system with 1, 2, or 3 PBC.…”
Section: Simulation Of Olympic Gel Systemsmentioning
confidence: 99%
“…al. 36 have shown that a conservative sampling rate of 4n crankshaft rotationsis adequate for polygons through 120 edges. In fact, a sampling rate of n crankshaft rotations is sufficient to achieve PCI values within one standard deviation of the random distribution without the closure condition.…”
Section: Measures Of Randomnessmentioning
confidence: 99%